Risk Factors and Prevalence of Forward Head Posture Complaints due to use of Devices during Pandemic - Savitri, Putri Annisa; Faidlullah, Hilmi Zadah (Ikatan Fisioterapi Indonesia, 2022)
Introduction: In March 2020, there were 1,528 confirmed cases of COVID-19 and 132 deaths, so the government implemented an online health and distance learning (PJJ) protocol. Due to the long use of this device, there are changes in the spine such as the Forward Head Posture. Objective To determine the prevalence rate and risk factors that cause Forward Head Posture complaints. Methods: This research is a quantitative research with analytical observational character which explains the correlation between variables through the Spearman Rank Statistical Test. The sample in this study were Physiotherapy students at UNISA Yogyakarta. Results: The prevalence of FHP in students (N = 87) was 61 people (70.1%) and the results from the Spearman Rank Statistical Test showed: (I) there was a correlation of FHP with posture p value of 0.004 (II) and a correlation in duration p value 0.000 (III) there is no correlation at age p value 0.142 and gender p value 0.920. Conclusion: There are 61 people out of 87 respondents experiencing Forward Head Posture and there is a significant correlation between posture and duration of using gadgets and there is no correlation between age and gender.